Determination of durability of samples modeling the MS-21 fuselage longitudinal and cross joints - V. K. Harina (Научный вестник МГТУ ГА)
Aircraft airworthiness maintenance is carried out by a number of measures guaranteeing safe operation. TsAGI, SibNIIA, GosNIIGA and other organizations with a highly-efficient laboratory base conduct tests and studies of structures and structural elements to determine or extend the operational life in stages. The tests require the capability to recreate complex loading spectra and they can be lengthy and expensive. One of the main problems encountered during testing is its forcing. Forcing reduces the test time while maintaining the equivalence of the fatigue damage and structural failure accumulation mechanisms under real and model loading. For every stage, the operational life limit and durability, guaranteeing flight safety, are determined on the basis of laboratory tests, operation tests and prediction of expected operating conditions. At every stage, information about the emerging defects is accumulated, additional tests are carried out and technical measures, determining the aircraft structure or structural elements operational life and durability, are developed, and design, manufacture, maintenance and repair deficiencies are identified. One of the key issues is the fracture mechanics, which the assessment of the aircraft structures survivability is based on. The fatigue failure mechanism depends on many factors: operational load or its model; stress condition that occurs during testing; the material, which the structural elements are made of. Fatigue failure begins with the microcracks in the structural element weakened area. Under the loads action, often being a random process, the cracks propagation is quite intense and it leads to the destruction of the structure. To determine the durability of the samples, modeling the MS-21 fuselage longitudinal and cross joints, theoretical calculations and experimental studies were carried out, and it allowed to judge about the compliance of the results obtained by the loaded hole.